2021
DOI: 10.51253/pafmj.v71i5.3864
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practice of Physical Activity Among Male Medical Undergraduates at Majmaah University, Saudi Arabia

Abstract: Objective: To probe the level of awareness and practice of the WHO recommendation for physical activity among male medical undergraduates at Majmaah University, Saudi Arabia. Study Design: Cross-sectional analytical study. Place and Duration of Study: College of Medicine, Majmaah University, Kingdom of Saudia Arabia from Oct to Dec 2018. Methodology: The study was conducted amongst 150 undergraduate medical students using a self-validated questionnaire. Results: A total of 53 (35.33%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…e j is the distribution of the center of gravity of the athlete's body when performing doubles. 5 The vector H represents the gravity force vector output by the table tennis doubles. From this, it can be concluded that the joint force moment of the table tennis player is:…”
Section: Strength Characteristics Of Table Tennis Playersmentioning
confidence: 99%
“…e j is the distribution of the center of gravity of the athlete's body when performing doubles. 5 The vector H represents the gravity force vector output by the table tennis doubles. From this, it can be concluded that the joint force moment of the table tennis player is:…”
Section: Strength Characteristics Of Table Tennis Playersmentioning
confidence: 99%